Education for Teachers of Library Science - Parkhi, R. S. (Journal of Information and Knowledge, 1966)
Points out that the increasing purpose of library service calls for a reorientation of university education and for the education of teachers of library science in the methods of education. Mentions the advantages to be gained through such a planned programme of development. Recommends the early implementation of the suggestions in the report of the Library Science Course Committee of the UGC.